A Triple Threat: A Case Report Detailing Surgical Management for Hypertrophic Cardiomyopathy, Flail Mitral Valve and Severe Pulmonary Hypertension - Cass G. G. Sunga; Kai-Chun Yang; Shakirat Oyetunji; Erik R. Swenson; Kavita Khaira (Reports)
The combination of hypertrophic cardiomyopathy with outflow tract obstruction, severe pre-capillary and post-capillary pulmonary hypertension, and severe primary mitral regurgitation is rare and presents distinct management challenges. Background and Clinical Significance: Pulmonary hypertension is an independent predictor of all-cause mortality in patients with hypertrophic cardiomyopathy managed medically and often precludes patients from undergoing cardiopulmonary bypass due to increased surgical morbidity and mortality. In studies specifically evaluating surgical myectomy, however, survival is favorable in patients with moderate-to-severe pulmonary hypertension. Case Presentation: We present a case of a 74-year-old male with six months of dyspnea with minimal exertion. A diagnostic work-up with transthoracic echocardiogram showed asymmetric left ventricular hypertrophy, left ventricular outflow tract obstruction with a peak gradient of 200 mmHg, right ventricular systolic pressure of 99 mmHg, systolic anterior motion of the mitral valve and flail anterior mitral leaflet. The patient was evaluated by a multi-disciplinary team and underwent extended septal myectomy and mitral valve repair with significant improvement in functional capacity post-operatively. Conclusions: While pulmonary hypertension increases the risk of morbidity and mortality during cardiopulmonary bypass, moderate-to-severe pulmonary hypertension in hypertrophic cardiomyopathy with outflow tract obstruction is a unique indication for septal reduction therapy that may not be associated with higher surgical mortality.